Indian Workers on the Home Front, 1940 (1940)
1940 1939-1945 "Indian Workers on the Home Front, 1940" [HFR0090], 1940 The Indian subcontinent (present-day India, Pakistan, Bangladesh and Sri Lanka) contributed 2.5 million servicemen and women, the largest volunteer army in history, to the Allied cause during the Second World War. In addition, it is estimated that some 14 million Indians took part in other forms of war work, notably as merchant seamen, air services ground staff, munitions workers and nurses.